Antibacterial ABS (Acrylonitrile Butadiene Styrene) material and preparation method thereof
By introducing silicon-containing modified benzooxazine, quaternary phosphonium salt-modified epoxy chitosan and other components into ABS materials, and using twin-screw extrusion and flat-plate vulcan molding processes, the shortcomings of existing ABS materials in flame retardant, antibacterial and tensile resistance effects are solved, and the multiple performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202510033117.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ABS materials have shortcomings in flame retardant, antibacterial and tensile resistance, which limits their application areas.
Antibacterial ABS material was prepared by extruding and granulating acrylonitrile-butadiene-styrene copolymer, silicon-containing modified benzooxazine, quaternary phosphonium salt modified epoxy chitosan and calcium carbonate in a twin-screw extruder and molding in a flat plate vulcanizer.
The antibacterial ABS material has been improved in antibacterial, flame retardant and tensile resistance, significantly expanding its application areas.
Smart Images

Figure BDA0005234732470000081 
Figure BDA0005234732470000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to an antibacterial ABS material and a preparation method thereof. Background Art
[0002] ABS material, the full name of which is acrylonitrile-butadiene-styrene copolymer, is a thermoplastic widely used in industry and daily life. It is made of three monomers, acrylonitrile, 1,3-butadiene and styrene, through graft copolymerization. However, its flame retardant and antibacterial effects are poor, which greatly limits its application areas. Therefore, how to avoid this phenomenon is the key to solving the problem.
[0003] For example, patent CN114031887A discloses a modified ABS material and a preparation method thereof. The modified ABS material greatly improves the chemical resistance through the action of a chemical resistance regulator and a surface modifier, but its antibacterial and flame retardant effects are not improved. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the deficiencies in the prior art, the present invention provides an antibacterial ABS material and a preparation method thereof, which has good antibacterial, flame retardant and tensile resistance effects.
[0006] (II) Technical solution
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an antibacterial ABS material, comprising the following components by weight: 40-70 parts by weight of acrylonitrile-butadiene-styrene copolymer, 6-10 parts by weight of silicon-modified benzoxazine, 4-8 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 1-2 parts by weight of calcium carbonate.
[0008] Preferably, the preparation method of the silicon-modified benzoxazine is:
[0009] Step 1: Add L-arginine and pentaerythritol methylsilicate to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, react at 90-110° C. for 5-7 hours, and then distill under reduced pressure, wash and dry to obtain intermediate 1;
[0010] Step 2: 8-10 parts by weight of the intermediate 1, 16-25 parts by weight of an aqueous solution of formaldehyde, and 11-14 parts by weight of magnolol are added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 75-95° C. After the reaction is completed, the mixture is distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine;
[0011] Step 3: Add 0.2-0.4 parts by weight of emulsifier sodium dodecyl sulfate and 2-4 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 5-9 parts by weight of styrene, 4-8 parts by weight of acryl alcohol, 3-7 parts by weight of dimethyldiallylammonium chloride and 5-6 parts by weight of olefinated benzoxazine, stir evenly, and then dropwise add 0.02-0.04 parts by weight of azobisisobutyronitrile initiator in a nitrogen atmosphere, react for 3-5 hours, filter the solvent after reaction, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine.
[0012] Preferably, in step 1, the mass ratio of L-arginine, pentaerythritol methyl silicate and p-toluenesulfonic acid catalyst is 1:0.9-1.2:0.01-0.02.
[0013] Preferably, the reaction time in step 2 is 8-12 hours.
[0014] Preferably, the reaction temperature in step three is 80-90°C.
[0015] Preferably, the preparation method of the quaternary phosphonium salt modified epoxy chitosan is:
[0016] S1. 0.68-0.72 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.01-0.03 g of initiator 1-hydroxybenzotriazole-hydrate was added to react for 0.4-0.6 h, and then 0.3-0.5 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 70-90 ° C for 12-14 h, and then 0.5-0.9 g of acrylic acid was added, and the reaction was continued for 40-50 min. After the reaction, the reaction was dialyzed for 2-3 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan;
[0017] S2. Add the modified chitosan into N,N-dimethylformamide solvent, stir evenly, then add aqueous hydrogen peroxide solution, react at 20-25°C for 3-6 hours, and then distill under reduced pressure, filter and dry to obtain quaternary phosphonium salt modified epoxy chitosan.
[0018] Preferably, the mass ratio of the modified chitosan to the aqueous hydrogen peroxide solution in S2 is 1:2.2-2.5.
[0019] Preferably, the preparation method of the antibacterial ABS material is: acrylonitrile-butadiene-styrene copolymer, silicon-modified benzoxazine, quaternary phosphonium salt-modified epoxy chitosan, and calcium carbonate are extruded and granulated at 180-190° C. in a twin-screw extruder, and then the granules are compression molded in a flat vulcanizer at a pressure of 8-9 MPa and 185-190° C. to obtain the antibacterial ABS material.
[0020] (III) Beneficial technical effects
[0021] The invention obtains the antibacterial ABS material by extruding acrylonitrile-butadiene-styrene copolymer, silicon-modified benzoxazine, quaternary phosphonium salt-modified epoxy chitosan and calcium carbonate in a twin-screw extruder for granulation, and then molding the granules in a flat vulcanizer.
[0022] During the extrusion process, the hydroxyl groups in the silicon-modified benzoxazine will undergo a ring-opening reaction with the epoxy groups in the quaternary phosphonium salt-modified epoxy chitosan, resulting in cross-linking between them, which increases their compatibility. At the same time, they continue to entangle with the acrylonitrile-butadiene-styrene copolymer, forming a tight cross-linking network between the three, which increases the mechanical properties of the material. The carbon nanotubes in the silicon-modified benzoxazine themselves also have good mechanical properties.
[0023] The silicon element and benzoxazine in silicon-modified benzoxazine have good flame retardant effect. The silicon element contained in it can form a glass-like substance on the surface of the material when burning, which hinders the material transfer and energy transport between the air and the substrate, and has a flame retardant effect. In addition, benzoxazine will form a heat-resistant phenolic resin structure at high temperature, which makes it have a good flame retardant effect; the chitosan in the quaternary phosphonium salt modified epoxy chitosan not only has a flame retardant effect, but also has a good antibacterial effect. The quaternary ammonium salt group in silicon-modified benzoxazine also has a good antibacterial effect. DETAILED DESCRIPTION
[0024] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics", Vol. 23, No. 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes":
[0025] Add 0.3 g of multi-walled carbon nanotubes to 30 mL of 98% concentrated sulfuric acid and 10 mL of 70% concentrated nitric acid, reflux at 140°C for 1 h, filter and wash. Weigh 0.1 g of the acidified carbon nanotubes obtained and disperse them in 15 mL of acetone and 15 mL of chloroform. Add 2 mL of triethylamine and 5 mL of acryloyl chloride, react at 40°C for 24 h, add 10 mL of ethanol and stir for 2 h, filter and wash to obtain vinyl carbon nanotubes.
[0026] Example 1
[0027] (1) adding L-arginine and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-arginine, pentaerythritol methyl silicate, and p-toluenesulfonic acid catalyst is 1:0.9:0.01, reacting at 90° C. for 5 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 1;
[0028] (2) 8 parts by weight of the intermediate 1, 16 parts by weight of an aqueous solution of formaldehyde, and 11 parts by weight of magnolol were added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 75° C. for 8 h. After the reaction, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine;
[0029] (3) Add 0.2 parts by weight of an emulsifier, sodium dodecyl sulfate, and 2 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 5 parts by weight of styrene, 4 parts by weight of acryl alcohol, 3 parts by weight of dimethyldiallylammonium chloride, and 5 parts by weight of olefinated benzoxazine, and after uniform stirring, add 0.02 parts by weight of azobisisobutyronitrile initiator dropwise in a nitrogen atmosphere, and react at 80° C. for 3 h. After the reaction is completed, filter the solvent, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine;
[0030] (4) 0.68 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.01 g of initiator 1-hydroxybenzotriazole monohydrate was added to react for 0.4 h, and then 0.3 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 70° C. for 12 h, and then 0.5 g of acrylic acid was added, and the reaction was continued for 40 min. After the reaction was completed, the reaction was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan;
[0031] (5) adding the modified chitosan to N,N-dimethylformamide solvent, stirring evenly, and then adding hydrogen peroxide aqueous solution thereto, wherein the mass ratio of the modified chitosan to the hydrogen peroxide aqueous solution is 1:2.2, reacting at 20° C. for 3 h, and then distilling under reduced pressure after the reaction, filtering and drying to obtain quaternary phosphonium salt modified epoxy chitosan;
[0032] (6) 40 parts by weight of acrylonitrile-butadiene-styrene copolymer, 6 parts by weight of silicon-modified benzoxazine, 4 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 1 part by weight of calcium carbonate are extruded and granulated at 180° C. in a twin-screw extruder, and the granules are then compression molded in a flat vulcanizer at a pressure of 8 MPa and at 185° C. to obtain an antibacterial ABS material.
[0033] Example 2
[0034] (1) adding L-arginine and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-arginine, pentaerythritol methyl silicate, and p-toluenesulfonic acid catalyst is 1:1.2:0.02, reacting at 110° C. for 7 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 1;
[0035] (2) adding 10 parts by weight of the intermediate 1, 25 parts by weight of an aqueous solution of formaldehyde, and 14 parts by weight of magnolol to a toluene solvent, fully dissolving them, and carrying out a cyclization reaction at 95° C. for 12 h. After the reaction, the reaction was distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine;
[0036] (3) Add 0.4 parts by weight of emulsifier sodium dodecyl sulfate and 4 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 9 parts by weight of styrene, 8 parts by weight of acryl alcohol, 7 parts by weight of dimethyldiallylammonium chloride and 6 parts by weight of olefinated benzoxazine, stir evenly, and then dropwise add 0.04 parts by weight of azobisisobutyronitrile initiator in a nitrogen atmosphere, react at 90° C. for 5 h, filter the solvent after reaction, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine;
[0037] (4) 0.72 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.03 g of initiator 1-hydroxybenzotriazole monohydrate was added to react for 0.6 h, and then 0.5 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 90° C. for 14 h, and then 0.9 g of acrylic acid was added, and the reaction was continued for 50 min. After the reaction was completed, the reaction was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan;
[0038] (5) adding the modified chitosan to N,N-dimethylformamide solvent, stirring evenly, and then adding hydrogen peroxide aqueous solution thereto, wherein the mass ratio of the modified chitosan to the hydrogen peroxide aqueous solution is 1:2.5, reacting at 25° C. for 6 h, and then distilling under reduced pressure after the reaction, filtering and drying to obtain quaternary phosphonium salt modified epoxy chitosan;
[0039] (6) 70 parts by weight of acrylonitrile-butadiene-styrene copolymer, 10 parts by weight of silicon-modified benzoxazine, 8 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 2 parts by weight of calcium carbonate are extruded and granulated at 190° C. in a twin-screw extruder, and the granules are then compression molded in a flat vulcanizer at a pressure of 9 MPa and at 190° C. to obtain an antibacterial ABS material.
[0040] Example 3
[0041] (1) adding L-arginine and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-arginine, pentaerythritol methyl silicate, and p-toluenesulfonic acid catalyst is 1:1.1:0.01, reacting at 100° C. for 6 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 1;
[0042] (2) adding 9 parts by weight of the intermediate 1, 20 parts by weight of an aqueous solution of formaldehyde, and 13 parts by weight of magnolol to a toluene solvent, fully dissolving them, and carrying out a cyclization reaction at 85° C. for 10 h. After the reaction, the reaction was distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine;
[0043] (3) Add 0.3 parts by weight of emulsifier sodium dodecyl sulfate and 3 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 7 parts by weight of styrene, 6 parts by weight of acryl alcohol, 5 parts by weight of dimethyldiallylammonium chloride and 6 parts by weight of olefinated benzoxazine, stir evenly, and then dropwise add 0.03 parts by weight of azobisisobutyronitrile initiator in a nitrogen atmosphere, react at 85° C. for 4 hours, filter the solvent after reaction, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine;
[0044] (4) 0.68 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.02 g of initiator 1-hydroxybenzotriazole monohydrate was added to react for 0.56 h, and then 0.4 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 80° C. for 13 h, and then 0.8 g of acrylic acid was added, and the reaction was continued for 45 min. After the reaction was completed, the reaction was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan;
[0045] (5) adding the modified chitosan to N,N-dimethylformamide solvent, stirring evenly, and then adding hydrogen peroxide aqueous solution thereto, wherein the mass ratio of the modified chitosan to the hydrogen peroxide aqueous solution is 1:2.4, reacting at 22° C. for 5 h, and then distilling under reduced pressure after the reaction, filtering and drying to obtain quaternary phosphonium salt modified epoxy chitosan;
[0046] (6) 60 parts by weight of acrylonitrile-butadiene-styrene copolymer, 8 parts by weight of silicon-modified benzoxazine, 6 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 1 part by weight of calcium carbonate are extruded and granulated at 185° C. in a twin-screw extruder, and the granules are then compression molded in a flat vulcanizer at a pressure of 8 MPa and at 187° C. to obtain an antibacterial ABS material.
[0047] Example 4
[0048] (1) adding L-arginine and pentaerythritol methyl silicate to N,N-dimethylformamide solvent, stirring and mixing, and continuously adding p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of L-arginine, pentaerythritol methyl silicate, and p-toluenesulfonic acid catalyst is 1:0.9:0.01, reacting at 90° C. for 5 h, and then distilling under reduced pressure, washing, and drying to obtain intermediate 1;
[0049] (2) 8 parts by weight of the intermediate 1, 16 parts by weight of an aqueous solution of formaldehyde, and 11 parts by weight of magnolol were added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 75° C. for 8 h. After the reaction, the mixture was distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine;
[0050] (3) Add 0.4 parts by weight of emulsifier sodium dodecyl sulfate and 4 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 9 parts by weight of styrene, 8 parts by weight of acryl alcohol, 7 parts by weight of dimethyldiallylammonium chloride and 6 parts by weight of olefinated benzoxazine, stir evenly, and then dropwise add 0.04 parts by weight of azobisisobutyronitrile initiator in a nitrogen atmosphere, react at 90° C. for 5 h, filter the solvent after reaction, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine;
[0051] (4) 0.72 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.03 g of initiator 1-hydroxybenzotriazole monohydrate was added to react for 0.6 h, and then 0.5 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 90° C. for 14 h, and then 0.9 g of acrylic acid was added, and the reaction was continued for 50 min. After the reaction was completed, the reaction was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan;
[0052] (5) adding the modified chitosan to N,N-dimethylformamide solvent, stirring evenly, and then adding hydrogen peroxide aqueous solution thereto, wherein the mass ratio of the modified chitosan to the hydrogen peroxide aqueous solution is 1:2.4, reacting at 22° C. for 5 h, and then distilling under reduced pressure after the reaction, filtering and drying to obtain quaternary phosphonium salt modified epoxy chitosan;
[0053] (6) 60 parts by weight of acrylonitrile-butadiene-styrene copolymer, 8 parts by weight of silicon-modified benzoxazine, 6 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 1 part by weight of calcium carbonate are extruded and granulated at 185° C. in a twin-screw extruder, and the granules are then compression molded in a flat vulcanizer at a pressure of 8 MPa and at 187° C. to obtain an antibacterial ABS material.
[0054] Comparative Example 1
[0055] This comparative example is different from Example 4 in that no silicon-modified benzoxazine is added.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 4 is that no quaternary phosphonium salt-modified epoxy chitosan is added.
[0058] A Staphylococcus aureus liquid with a concentration of 2×108 CFU / mL was added as a test strain to a sterilized culture dish, and then a solid agar medium was added and dissolved, cooled to 45°C, and then poured into a culture dish, 20 mL was poured into each plate with an inner diameter of 10 cm, and then the antibacterial materials of the embodiments of the present invention and the comparative example (with a diameter of 3 cm and a thickness of 1 mm) were placed on the culture plate, and cultured in a constant temperature incubator for 12 hours at a temperature of 37°C. After culture, the diameter of the inhibition zone was measured. The test results are shown in Table 1.
[0059] Table 1: Antimicrobial testing.
[0060] project Diameter of inhibition zone (mm) Example 1 15.4 Example 2 16.8 Example 3 16.5 Example 4 16.3 Comparative Example 1 12.7 Comparative Example 2 11.9
[0061] It can be seen from Table 1 that the antibacterial ABS material Examples 1-4 of the present invention have better antibacterial effects than Comparative Examples 1-2.
[0062] An electronic universal testing machine was used to test the tensile properties of the material. The test results are shown in Table 2.
[0063] Table 2: Tensile properties tested.
[0064]
[0065]
[0066] It can be seen from Table 2 that the antibacterial ABS material embodiments 1-4 of the present invention have better tensile properties than comparative examples 1-2, and therefore have better mechanical properties.
[0067] Use an oxygen index meter to test the limiting oxygen index of the material; use a horizontal and vertical combustion instrument to test the combustion level of the material.
[0068] Table 3: Flame retardancy test.
[0069] project Limiting oxygen index (%) Combustion level Example 1 30 V-0 Example 2 32 V-0 Example 3 32 V-0 Example 4 31 V-0 Comparative Example 1 20 V-1 Comparative Example 2 21 V-1
[0070] It can be seen from Table 3 that the flame retardant effect of Examples 1-4 is better than that of Comparative Examples 1-2, which indicates that the antibacterial ABS material prepared by the present invention has a good flame retardant effect.
[0071] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An antibacterial ABS material, characterized in that: The invention comprises the following components by weight: 40-70 parts by weight of acrylonitrile-butadiene-styrene copolymer, 6-10 parts by weight of silicon-modified benzoxazine, 4-8 parts by weight of quaternary phosphonium salt-modified epoxy chitosan, and 1-2 parts by weight of calcium carbonate.
2. The antibacterial ABS material according to claim 1, characterized in that: The preparation method of the silicon-modified benzoxazine is as follows: Step 1: Add L-arginine and pentaerythritol methylsilicate to N,N-dimethylformamide solvent, stir and mix, continue to add p-toluenesulfonic acid catalyst, react at 90-110° C. for 5-7 hours, and then distill under reduced pressure, wash and dry to obtain intermediate 1; Step 2: 8-10 parts by weight of the intermediate 1, 16-25 parts by weight of an aqueous solution of formaldehyde, and 11-14 parts by weight of magnolol are added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 75-95° C. After the reaction is completed, the mixture is distilled under reduced pressure, washed with deionized water, and dried to obtain an olefinated benzoxazine; Step 3: Add 0.2-0.4 parts by weight of emulsifier sodium dodecyl sulfate and 2-4 parts by weight of vinyl carbon nanotubes to deionized water, and after uniform dispersion, add 5-9 parts by weight of styrene, 4-8 parts by weight of acryl alcohol, 3-7 parts by weight of dimethyldiallylammonium chloride and 5-6 parts by weight of olefinated benzoxazine, stir evenly, and then dropwise add 0.02-0.04 parts by weight of azobisisobutyronitrile initiator in a nitrogen atmosphere, react for 3-5 hours, filter the solvent after reaction, wash with deionized water and ethanol in turn, and dry to obtain silicon-modified benzoxazine.
3. The antibacterial ABS material according to claim 2, characterized in that: In the step 1, the mass ratio of L-arginine, pentaerythritol methyl silicate and p-toluenesulfonic acid catalyst is 1:0.9-1.2:0.01-0.
02.
4. The antibacterial ABS material according to claim 2, characterized in that: The reaction time in step 2 is 8-12 hours.
5. The antibacterial ABS material according to claim 2, characterized in that: The reaction temperature in step 3 is 80-90°C.
6. The antibacterial ABS material according to claim 1, characterized in that: The preparation method of the quaternary phosphonium salt modified epoxy chitosan is: S1. 0.68-0.72 g of chitosan was dissolved in a 1% acetic acid solution, and then 0.01-0.03 g of initiator 1-hydroxybenzotriazole-hydrate was added to react for 0.4-0.6 h, and then 0.3-0.5 g of (3-carboxypropyl) triphenylphosphonium bromide was added thereto, and nitrogen was introduced for protection, and the reaction was carried out at 70-90 ° C for 12-14 h, and then 0.5-0.9 g of acrylic acid was added, and the reaction was continued for 40-50 min. After the reaction, the reaction was dialyzed for 2-3 days using a dialysis bag with a molecular weight cutoff of 3500 to obtain modified chitosan; S2. Add the modified chitosan into N,N-dimethylformamide solvent, stir evenly, then add aqueous hydrogen peroxide solution, react at 20-25°C for 3-6 hours, and then distill under reduced pressure, filter and dry to obtain quaternary phosphonium salt modified epoxy chitosan.
7. The antibacterial ABS material according to claim 6, characterized in that: The mass ratio of the modified chitosan to the aqueous hydrogen peroxide solution in S2 is 1:2.2-2.
5.
8. A method for preparing the antibacterial ABS material according to any one of claims 1 to 7, characterized in that: The preparation method of the antibacterial ABS material comprises the following steps: extruding acrylonitrile-butadiene-styrene copolymer, silicon-modified benzoxazine, quaternary phosphonium salt-modified epoxy chitosan and calcium carbonate in a twin-screw extruder at 180-190° C. to form granules, and then molding the granules in a flat vulcanizer at 185-190° C. under a pressure of 8-9 MPa to obtain the antibacterial ABS material.
Citation Information
Patent Citations
Quaternary phosphonium chitosan and application of quaternary phosphonium chitosan serving as vaccine immune adjuvant
CN107200788A
Full-biomass-based benzoxazine monomer as well as preparation method and application thereof
CN117551051A
Bioderived monomers for the generation of polybenzoxazine thermosets and thermoplastics
US20240343698A1